Integrated Assessment of Phenotypic Traits and Bioactive Compounds in Astragalus membranaceus var. mongholicus - Yaqi Liu; Xiu Wang; Mingxin Zhang; Fuxin Li; Yaoyao Wang; Yu Feng; Haitao Yu; Yang Gu; Jiushi Liu; Weiwei Gao (Horticulturae)
Astragalus membranaceus var. mongholicus (AMM) is a widely used medicinal plant in China, primarily cultivated in the northern regions; however, the selection and breeding of superior varieties remains underdeveloped. To scientifically assess the germplasm resources of AMM and facilitate its breeding, this study collected 33 germplasm samples from five provinces and conducted a comprehensive evaluation of their botanical traits, agronomic traits, quality traits, and powdery mildew resistance. The results indicated that, among the 18 botanical and agronomic traits, the Shannon–Wiener diversity index (H′) for quantitative traits was higher than that for qualitative traits, with the coefficient of variation ranging from 6.82% to 34.14%. The characterization of five flavonoids and eight saponins based on the established UPLC-Q-TOF/MS technique revealed that 13 compounds showed significant abundance variations across germplasms. Correlation analysis revealed that plants with robust above-ground growth usually have higher yields. Moreover, the number of compound leaflets was positively correlated with flavonoid content in the roots, whereas germplasms with smaller above-ground biomass and thinner roots exhibited higher saponin content. Based on the comprehensive scores (F-value), the top three germplasms were An-31, An-26, and An-28, which may serve as promising breeding materials. Cluster analysis grouped the 33 germplasms into five categories, including high-content and high-yield groups. Five germplasms exhibiting strong disease resistance were identified, with An-26 demonstrating the best performance in yield, quality, and resistance. Furthermore, a negative correlation was observed between powdery mildew resistance and flavonoid content in roots. This study will provide a foundation for the AMM breeding and selection.